Coverage and quality radio analysis for circuit-switch fallback in long term evolution (LTE) / Mohd Shahidi Yusof - Yusof, Mohd Shahidi (2014)
This rapid growth of technologies is forcing network operators to upgrade the network to LTE (Long Term Evolution), a 4th generation of mobile network. However, the LTE does not support circuit switch network and only depend on the IP Multimedia Subsystem (IMS) for offering voice and Short Messaging Service (SMS). The CS Fallback in E-Packet System (EPS) allows the provisioning of voice call and other CS domain (E.g. SMS, CS UDI video/USSD/LCS) by reuse of CS domain infrastructure when the UE is served in LTE domain. A CS Fallback allows UE that connect to E-UTRAN will use GERAN/UTRAN to connect to the CS domain. This paper is comparing different technique of handling VoLTE and analyzes one of the approaches (CS Fallback). The performance of the CS Fallback was studied in term of coverage and quality. This experiment demonstrate that in good optimized network, the CS Fallback from LTE to UMTS call setup success rate can be very close to those achieve in the circuit switch systems.